Analysis of Students' Combinatorial Thinking Model in Solving Combinatorics Problems - Desfitri, Rita (KnE Social Sciences, 2024)
The purpose of this study was to analyze students’ combinatorial thinking in solving combinatorics problems. This study was organized into two related areas. The first focused on whether students applied combinatorial thinking in Lockwoods’ model, and the second emphasized on students’ ability in solving the given combinatorics problems. This research method used was a qualitative descriptive method. Participants of this study were students majoring mathematics education at Bung Hatta University who took combinatorics courses. Five combinatorics problems were given to the students and then analyzed. The result showed that based on Lockwoods’ model, the aspect of combinatorial thinking that was more widely applied in solving combinatorics problems was the counting process. However, most students who were able to solve problems quite well, and tended to solve problems with steps from formulating, followed by the process of counting to reach a set outcome. Whereas students who did the counting process stage without formulating problems into mathematics expressions, generally checked a set of outcomes by trial and errors. It can also be noted that in general, f/or any problem given, the percentage of students who faced difficulties when formulating problems into mathematical expressions or on the counting process was more that 50%, and the number of students who reached the correct set of outcomes was relatively low. Keywords: student, combinatorial thinking model, solving combinatorics problems